Artificial Intelligence-Based Learning Media in Islamic Religious Education Learning - Zain, Irfan Ahmad; Muslih, Hafid; Maulana, Ahmad Nanda; Azizah, Habibah Nur; Hakiki, Kiki Miftahul (LifeSciFi, 2025)
The rapid development of digital technology in the modern era has significantly transformed the education sector, including Islamic Religious Education (IRE). The integration of artificial intelligence (AI) emerges as an innovation that supports adaptive, effective, and learner-centred learning while redefining teachers’ roles as agents of educational transformation. This study aims to examine the concepts, applications, opportunities, and challenges of AI integration in IRE learning, with particular attention to teachers’ innovative orientation. The research employs a qualitative approach through library research by reviewing relevant scientific literature. The findings indicate that AI can enhance IRE learning by enabling personalized instruction, providing rapid feedback, and offering interactive learning experiences aligned with the characteristics of the digital generation. Nevertheless, several challenges remain, including limited technological infrastructure, gaps in teachers’ digital literacy, and the potential reduction of human interaction between teachers and students. In conclusion, teacher innovation is a crucial factor in optimizing the use of AI in Islamic education. Teachers are expected to act as facilitators, learning designers, and drivers of innovation who are able to integrate Islamic values with technological advancement to ensure that Islamic education remains relevant and competitive in the digital era.